Safety of Tirofiban in acute ischemic stroke: the SaTIS trial - Siebler, Mario; Hennerici, Michael G.; Schneider, Dietmar; Reutern, Gerhard M. von; Seitz, Rüdiger J.; Röther, Joachim; Witte, Otto W.; Hamann, Gerhard; Junghans, Ulrich; Villringer, Arno; Fiebach, Jochen B. (Stroke, 2011)
Background and Purpose: Tirofiban is a highly selective, fast-acting nonpeptide glycoprotein IIb/IIIa platelet receptor antagonist with a short half-life time. Glycoprotein IIb/IIIa antagonists are effective for the treatment of acute coronary syndromes proven in large clinical trials. Safety and efficacy in patients with ischemic stroke are uncertain. This was addressed in the Safety of Tirofiban in acute Ischemic Stroke (SaTIS) trial. Methods: Two hundred sixty patients with acute ischemic stroke were randomized in a placebo-controlled, prospective, open-label treatment, blinded outcome reading multicenter trial. Subjects with a National Institutes of Health Stroke Scale between 4 and 18 received intravenously either tirofiban or placebo within 3 to 22 hours after symptom onset for 48 hours. The primary end point was the rate of cerebral bleeding as measured in follow-up CT scans 2 to 7 days after inclusion. The secondary end point was clinical efficacy within 1 week (National Institutes of Health Stroke Scale, modified Rankin Scale) and after 5 months (Barthel Index, modified Rankin Scale)Results: The rate of cerebral hemorrhagic transformation (I/II) and parenchymal hemorrhage (I/II) did not differ between both groups (tirofiban 36 of 120; placebo 33 of 124: OR, 1.18; 95% CI, 0.66 to 2.06). Mortality after 5 months was significantly lower in patients treated with tirofiban (3 of 130 [2.3%] versus 11 of 126 [8.7%]; OR, 4.05; 95% CI, 1.1 to 14.9). No difference in neurological/functional outcome was found after 1 week and after 5 months. Conclusions: We conclude that tirofiban might be safe in acute moderate ischemic stroke even when administered within a large time window after symptom onset and might save lives in the late outcome. Clinical Trial Registration: URL: www.strokecenter.org/trials/. Trial name: SaTIS. Enrollment began before July 1, 2005.